1999
DOI: 10.1172/jci6663
|View full text |Cite
|
Sign up to set email alerts
|

The role of intestinal P-glycoprotein in the interaction of digoxin and rifampin

Abstract: Marked interindividual variability in plasma concentrations of drugs after administration of a fixed dose is often related to differences in drug metabolism. Inhibition and induction of hepatic drug metabolism, and also of prehepatic biotransformation in the intestine, are important and well-established mechanisms for drug interactions. A number of clinical important drug interactions with rifampicin have been reported that are caused by its powerful induction of intestinal cytochrome P4503A4 (1, 2). We have o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

38
734
2
16

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 883 publications
(790 citation statements)
references
References 37 publications
38
734
2
16
Order By: Relevance
“…Considering that erlotinib is metabolized primarily by the CYP3A4 enzyme system (22) and that rifampicin and ketoconazole are wellknown CYP3A4 inducer and inhibitor, respectively, these drug-drug interactions have been considered as primarily CYP3A4 mediated. However, given that rifampicin has been shown to induce also intestinal P-gp (23,24) and that ketoconazole is a P-gp inhibitor (25,26), although the effects of these two drugs on CYP3A expression/activity are expected to be greater and therefore more clinically relevant compared with the modulation of P-gp, a potential contribution of ATP-binding cassette drug efflux transporters to these interactions cannot completely be excluded.…”
Section: Introductionmentioning
confidence: 99%
“…Considering that erlotinib is metabolized primarily by the CYP3A4 enzyme system (22) and that rifampicin and ketoconazole are wellknown CYP3A4 inducer and inhibitor, respectively, these drug-drug interactions have been considered as primarily CYP3A4 mediated. However, given that rifampicin has been shown to induce also intestinal P-gp (23,24) and that ketoconazole is a P-gp inhibitor (25,26), although the effects of these two drugs on CYP3A expression/activity are expected to be greater and therefore more clinically relevant compared with the modulation of P-gp, a potential contribution of ATP-binding cassette drug efflux transporters to these interactions cannot completely be excluded.…”
Section: Introductionmentioning
confidence: 99%
“…It is suggested that P-glycoprotein (P-gp) and/or CYP3A limit the oral bioavailability of digoxin, rifampin [4], vinblastine [5], dexamethasone tromethorphan [6], tacrolimus [7], sirolimus [8] and cyclosporin A [9,10]. Lown et al [11] suggested that P-glycoprotein…”
Section: Introductionmentioning
confidence: 99%
“…Although CYP3A in duodenal samples was enhanced 4.4-fold, there was no correlation between the AUC of digoxin and CYP3A4 expression of individual volunteers. 92 These data strongly indicate that P-gp modulates intestinal digoxin absorption, leading to low drug concentrations in individuals with high P-gp expression and high concentrations in those with low P-gp expression. 92 Accordingly, rifampin-mediated P-gp induction is associated with a reduction of plasma digoxin.…”
Section: Drug Interactions After Treatment With Rifampinmentioning
confidence: 81%
“…90,91 It was recently reported that concomitant administration of rifampin at a dose of 600 mg/day for 10 days in healthy volunteers reduced digoxin plasma concentrations substantially after an oral single-dose (1 mg) administration compared with the plasma-time profile without rifampin treatment. 92 The effect was less pronounced after intravenous administration of digoxin.…”
Section: Drug Interactions After Treatment With Rifampinmentioning
confidence: 97%